Uji antioksidan fitosom campuran buah kelapa (Cocos nucifera L.) sebagai agen immunonutrisi pada kondisi infeksi - Rahmayati Rusnedy (Riset Informasi Kesehatan, 2021)
Infections and parasitic diseases are the cause of most of the deaths of 13 million infants and children in developing countries due to malnutrition. The existence of resistance from the use of antibiotics is also a public health problem throughout the world in handling cases of infection. Formulas from natural ingredients that have strong antioxidant activity can be used to treat infections. It has been reported that phytosome formulations from natural ingredients provide protection and even increase antioxidant activity. Coconuts and kaffir limes are sources of polyphenols and other multicomponent compounds that are good for treating infections. Phytosomes which are also known as herbosomes can be prepared by the reflux method. The coconut flesh that has been mashed first is filtered to get the coconut milk and then added with 10:1 kaffir lime juice. The mixture was refluxed in 100 ml of distilled water for 2 hours at 40°C using a rotary vacuum evaporator equipped with a vacuum pump to obtain a thin film formation. Rotavapor speed is gradually increased from 100 to 180 rpm. The coating is kept in the refrigerator for up to 24 hours. After storage, the film was hydrated in phosphate buffer at pH 5.5 at 40°C. Phytosome suspension is formed and sonicated. The precipitate was taken and put into a desiccator. The phytosomes obtained were characterized for their physicochemical properties, morphology and particle size shape and were tested for antioxidant activity using the DPPH method. The phytosome formula 1:1 with very strong antioxidant activity with a value of 33.75 g/mL has the potential to be developed as an immunonutrient formula in cases of infection through antioxidant activity with an average particle size of ± 470 nm.